Profiling Chemical Literacy and 21st Century Skills: Efforts to Develop Effective Chemistry Learning Strategies in Public Schools - Laila Naufi Rachma; A.K Prodjosantoso (Eduvest - Journal of Universal Studies, 2026)
21st-century education demands a transformation towards student-centered learning, yet its implementation in new institutions like Sekolah Rakyat is often hindered by a lack of student profile data. This study aims to map the initial profile of 21st-century skills (4C) and chemical literacy of Grade X students at Sekolah Rakyat 19 Bantul as a diagnostic foundation for developing learning strategies. This study employed a quantitative survey method. The subjects were 40 students selected through total sampling technique. Data were collected using questionnaires for critical thinking, creative thinking, communication, and collaboration skills, as well as a test for chemical literacy skills. Data analysis used descriptive statistics to determine student ability categories. The results showed that communication skills were the most prominent aspect, with 62.5% of students in the high category. Critical thinking skills were dominated by the high category (52.5%), while creative thinking and collaboration skills were mostly in the medium category. Conversely, initial chemical literacy was the lowest aspect, with 67.5% of students in the medium category and 20% in the low category. This study concludes that there is a gap between strong social capital (communication) and low scientific literacy, recommending the implementation of differentiated and contextual chemistry learning strategies to address this disparity.